PERCEPTIONS OF HOW ORGANIZATIONAL STRUCTURE IMPACTS STUDENT PERFORMANCE IN A SOUTHEASTERN NORTH CAROLINA ALTERNATIVE SCHOOL - Graham, Cherié N. (East Carolina University, 2015)
The purpose of this study was to identify an appropriate structure to successfully serve all alternative students in an effort to increase the graduation rate and academic proficiency of the students at an alternative high school in rural southeastern North Carolina. The following research question was investigated: To what extent if any, were the alternative learning program standards implemented within the organizational structure to impact student performance? Both quantitative and qualitative research designs were used to gain insight into academic structures that serve at-risk or non-traditional students. The intent of the research was to define key components of alternative learning program standards that should be implemented with fidelity within the alternative school’s organizational structure to increase student performance, academic achievement, and graduation rates of at-risk students. Qualitative research encompassed both descriptive surveys and open-ended structured questionnaires that were utilized to conduct this study. Quantitative research included descriptive statistics and a compilation of the data collected from the survey results. Students, parents, faculty, administrators, and a community member participated in the study. According to Green and Cypress (2009), “the structure of the organization has to facilitate the change initiative. When an appropriate structure is in place, everyone is aware of who does what, when it is to be done, and who is accountable for the results.” Organizational structure involves leadership, culture and climate, resource allocation, programs, physical structure, and support systems of an organization (Baldy et al., 2014). NCDPI implemented standards that should be implemented with fidelity in all alternative schools—clear mission, leadership, culture and climate, professional development, parent/community involvement, curriculum and instruction, and monitoring and assessment (NCDPI, 2006). These standards are the foundation upon which alternative school’s organizational structure should be governed. The Academy of focus in this study had some components of the alternative learning program standards in operation; however, the student achievement data and graduation rates of those enrolled in the Academy suggests that the implementation strategies currently in place need to be revisited. While participants in the study felt that the Academy was meeting the needs of its students, the current model of the organizational structure has proven that the holistic needs of the students are not being met due to the lack of a clear mission and community/parental involvement, the curriculum and instruction currently offered to students, and the monitoring and assessment of students—particularly with regard to the support system currently in place.
Keywords: Organizational structure; Alternative schools--North Carolina; Organizational effectiveness--North Carolina; High school students--North Carolina; High school graduates--North Carolina--Statistics; Academic achievement--North Carolina